ANALISIS TINGKAT KESEJAHTERAAN, SIKAP, PERILAKU, DAN TINGKAT KEPUASAN KELUARGA SASARAN PROGRAM KONVERSI MINYAK TANAH KE LPG DI KOTA BEKASI - Muflikhati, Istiqlaliyah; Nurmayanti, Novida; Alfiasari, Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2010)
Substitution program of kerosene to LPG is one of the government programs, which is very important for energy policy in this country. The aims of this research were to analyze the socioeconomic characteristics of target family and to construct the strategies in order to increase the quality of program. The study was conducted using cross sectional design. It involved 60 families from two villages at Bekasi City as respondents. The result of the study showed that expenditure allocation for fuel in the family respondents decreased after the program. The family welfare was affected by decreasing of expenditures allocation for fuel, wives’s occupational status, wives’ educational level, and family’s attitude in this program. Meanwhile, wives’s occupational status and educational level also affected family’s attitude in the program. Moreover, family’s attitude in the program gave significant effect on the behavior of using LPG. Family’s Satisfaction level based on CSI showed that respondents were satisfied with this program.